Studia etanaica new texts and discussions - Kinnier Wilson, James V. (Ugarit-Verl., 2007)
J. Kinnier Wilson, author of "The Legend of Etana" (1985), offers a collection of commentaries and discussions on the Akkadian Epic of Etana, taking into consideration new fragments, new editions and new translations, which have been published during the last two decades. Thus, new light is shed among others on Etana's famous flights to heaven, the death of his wife Muanna and his own death.
Keywords: Etana (Epic); Etana-Mythos; Etana-epos (anoniem); Assyro-Babylonian literature -- History and criticism; Mesopotamië